2021
DOI: 10.1186/s40249-021-00916-2
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy and durability of Olyset® Plus, a permethrin and piperonyl butoxide-treated insecticidal net in a 3-year long trial in Kenya

Abstract: Background Long-lasting insecticide nets (LLINs) are a core malaria intervention. LLINs should retain efficacy against mosquito vectors for a minimum of three years. Efficacy and durability of Olyset® Plus, a permethrin and piperonyl butoxide (PBO) treated LLIN, was evaluated versus permethrin treated Olyset® Net. In the absence of WHO guidelines of how to evaluate PBO nets, and considering the manufacturer’s product claim, Olyset® Plus was evaluated as a pyrethroid LLIN. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
12
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
6
12
3
Order By: Relevance
“…Permethrin content in the PBO-LLINs and standard LLINs were halved after 36 months, while PBO was reduced by more than 95% of the initial concentration. These insecticidal contents were comparable to those reported after 36 months of use in a study conducted in Kenya [19] with the same brand of net. The faster reduction of PBO compared to pyrethroid was also observed in another community trial in Uganda [32] and similarly reported when nets were washed in laboratory conditions [33-35].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Permethrin content in the PBO-LLINs and standard LLINs were halved after 36 months, while PBO was reduced by more than 95% of the initial concentration. These insecticidal contents were comparable to those reported after 36 months of use in a study conducted in Kenya [19] with the same brand of net. The faster reduction of PBO compared to pyrethroid was also observed in another community trial in Uganda [32] and similarly reported when nets were washed in laboratory conditions [33-35].…”
Section: Discussionsupporting
confidence: 85%
“…The deterioration characteristics of pyrethroid-only LLINs cannot be extrapolated to dual-active-ingredient LLINs, because partner synergists or insecticides may degrade faster than pyrethroids. A household randomised trial from Kenya reported more than 80% of PBO was lost from PBO-LLINs after 3 years of use compared to 50% of the pyrethroid insecticide [19].…”
Section: Introductionmentioning
confidence: 99%
“…Both net types lasted for less than 2 years, which is a shorter timespan than has been see in other studies' for similar nets (16,18,32). Moreover, in this study, less than a third of the distributed nets remained in households after 3 years of community use, which is slightly lower than has been observed in other studies conducted in Tanzania (45%) (18), Mozambique (40%) (33), and Kenya (82%) (34).…”
Section: Discussioncontrasting
confidence: 60%
“…However, small number of nets has been tested for other net types than PBO nets (43); thus, for PBO nets this need to be repeated to confirm these results. Although, a study that assessed insecticide content of PBO nets on a number of nets 4 times higher than of this study, found a relatively similar reduction in chemical content(16). Importantly, this study does not report on entomological bio-efficacy meaning that we do not know whether the reduced chemical content on the nets over time would have also resulted in reduced mosquito mortality.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation